Hubungan Usia dan Frekuensi Ante Natal Care Dengan Kejadian Kehamilan Serotinus Di Wilayah Kerja Puskesmas Pasanea Kecamatan Seram Utara Barat - Siti Rochmaedah (STIKes Ibnu Sina Ajibarang, 2024)
Serotinus pregnancy is one of the causes that can increase the risk of perinatal death and morbidity 3 times compared to term pregnancy and serotinus is a health problem that is clinically important and treatment must be appropriate to reduce the risk of death in the mother and baby born. To know The relationship between age and frequency of ante natal care with the incidence of serotinous pregnancies in the Pasanea Community Health Center working area. This research is a descriptive analytical research with a retrospective approach. The population is mothers who gave birth with serotinus with a sample size of 65 respondents. The sampling technique uses total sampling with the analysis test used is chi-square. Statistical tests using Chi-Square showed that the ρ value was 0.018 where α < 0.05 so it could be concluded that statistically there was a significant relationship between age and the incidence of serotinous pregnancy, while the ANC frequency variable was known to have a ρ value of 0.164 where α > 0.05 and could It was concluded that statistically there was no significant relationship between age and the incidence of serotinus pregnancy in the working area of the Pasanea District Health Center. North West Seram. There is a relationship between age and the incidence of serotinous pregnancies, there is no relationship between the frequency of ANC and the incidence of serotinous pregnancies in the working area of the Pasanea District Health Center. North West Seram